The identification of knowledge gaps in the technologies of cyber-physical systems with recommendations for closing these gaps - Murray Sinclair; Carys Siemieniuch; Paul Palmer (2018)
The paper reports some training, education, and operational findings from an EU Horizon 2020 project that included the production of technology road‐maps for the domain of cyber‐physical systems (CPS). The project reviewed Deliverables from 72 CPS projects, all within Framework Programme 7 and Horizon 2020, including 18 from the ARTEMIS and ECSEL subprograms. This analysis led to the production of a “Knowledge Map” containing 75 technologies identified within the 72 projects as nodes in this map, connected by interoperability links. Filtering this map for each node, in turn, has led, in combination with other parts of the project, to some 48 recommendations for future focus and funding of developments in these technologies to assist in the rapid adoption of CPS in all domains. While the focus has been limited to European Union research and innovation, it is believed that the recommendations are transferable to other regions of the world.